Identificación y tratamiento de endoparásitos mediante diferentes técnicas en caballos de la Unidad de Equitación y Remonta Santiago de Guayaquil - Guamán Quingatuña, Marlon Santiago (2017)
The evaluation of the identification and treatment of endoparasites by different techniques in horses was carried out in the Province of Guayas between Duran Canton and Yahuachi, in the Riding and Unit of Santiago de Guayaquil; the objectives were;Determine the types of endoparasites by different techniques, measure the degree of parasitic infestation of equines, design the therapy and treatment of the identified parasites, verify the presence of endoparasites.In the experimental design a descriptive statistic was used, in addition to the t-student test, based on frequency tables, charts, histograms, since it is a medical diagnostic study.The number of animals under study is 50 equines, in regard to the laboratory techniques used for the identification of endoparasites we have in blood method; Microhematocrit method, in feces we have the Flotation Method with Sugar Solution; Sedimentation method with detergent solution; Graham method using adhesive tape. With regard to the results obtained in the investigation, we learned that using blood laboratory techniques was not found parasites, this can be deduced that due to good technical management of research animals there is no decline in their health, since hemoparasites can be observed when the animal under study is in a state of acute health; On the other hand in the coproparasitic examinations we have that in the Flotation Method, Sedimentation gives a positive result to Strongylus in the equines submitted to the study, on the other hand when analyzing the coproparasitic samples using the Graham method we did not find any parasite in all the analyzes processed.It is recommended to use PCR, IMMUNOFLUORESCENCE and ELISA techniques to be more effective in blood tests; also have a deworming schedule according to the type of parasite and its life cycle.